2018
DOI: 10.1117/1.oe.57.5.054117
|View full text |Cite
|
Sign up to set email alerts
|

Spectral correction algorithm for multispectral CdTe x-ray detectors

Abstract: Compared to the dual energy scintillator detectors widely used today, pixelated multispectral X-ray detectors show the potential to improve material identification in various radiography and tomography applications used for industrial and security purposes. However, detector effects, such as charge sharing and photon pileup, distort the measured spectra in high flux pixelated multispectral detectors. These effects significantly reduce the detectors' capabilities to be used for material identification, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…where kB is the Boltzmann's constant (= 1.38×10 -23 J/K), T is absolute temperature (= 313.15 K), z is the distance between the interaction location and the anode (along the direction of the electric field), d is the thickness of the detector, q is the elementary charge (= 1.60×10 -19 C), U is the bias voltage (= 1000 V), N is the number of electron-hole pairs liberated (= Edep/ΔE; Edep is energy deposited in each interaction and ΔE is the energy per electron-hole pair), 𝜀 is the permittivity, and 𝜎 / is the initial diameter of the charge cloud. 4 For 𝜎 / , another Monte Carlo simulation was designed, with a cubicle detector sized 50×50×50 mm 3 and a point source at its center that irradiated 10 5 electrons for each energy in the 1-150 keV range. The diameter covering 95% of the total charge was considered the initial charge cloud diameter (𝜎 / ) for the simulated detector material.…”
Section: B1 Detector Responsementioning
confidence: 99%
“…where kB is the Boltzmann's constant (= 1.38×10 -23 J/K), T is absolute temperature (= 313.15 K), z is the distance between the interaction location and the anode (along the direction of the electric field), d is the thickness of the detector, q is the elementary charge (= 1.60×10 -19 C), U is the bias voltage (= 1000 V), N is the number of electron-hole pairs liberated (= Edep/ΔE; Edep is energy deposited in each interaction and ΔE is the energy per electron-hole pair), 𝜀 is the permittivity, and 𝜎 / is the initial diameter of the charge cloud. 4 For 𝜎 / , another Monte Carlo simulation was designed, with a cubicle detector sized 50×50×50 mm 3 and a point source at its center that irradiated 10 5 electrons for each energy in the 1-150 keV range. The diameter covering 95% of the total charge was considered the initial charge cloud diameter (𝜎 / ) for the simulated detector material.…”
Section: B1 Detector Responsementioning
confidence: 99%
“…[53]. In this work we therefore use the correction algorithm proposed by Dreier et al [54] to correct the spectral distortions in the PCD used. The LAC curve is corrected by the correction of the measured flat field and attenuated spectra, for which the comprehensive semianalytical interpretations based on the physical reason of the different interactions are used.…”
Section: Data Correction and Energy Bins Rebinningmentioning
confidence: 99%
“…In a recent paper [53] we showed that the correction of the detector's spectral response for these distortions is required to correct the measured LACs and significantly enhance the material classification performance. A correction algorithm presented by Dreier et al [54] was used to correct for the spectral distortions occurring in the PCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of electron/hole pairs created is proportional to the energy deposited [3,4]. One of the limitations of HPDs is the intrinsic X-ray fluorescence (XRF) emission from the detector semiconductor sensor [5]. These fluorescence photons can travel away from the initial interaction position and can interact in neighbouring pixels or even escape the detector.…”
mentioning
confidence: 99%